Psychological Capital terhadap Subjective Well Being: Moderasi Work Engagement - Arsyawal .; Ririn Handayani; Adolf Bastian (CV. ITTC INDONESIA, 2025)
The main issue addressed in this study is how psychological capital can influence judges' subjective well-being and the extent to which job engagement can strengthen or weaken this relationship. High subjective well-being is crucial for improving the quality of judges' decisions and performance, but the precise role of job engagement in this relationship remains unknown. The study was conducted on all judges in Riau Province with the aim of examining work engagement in moderating the influence of psychological capital on subjective well-being. The study population consisted of 80 judges. Based on this population size, the entire population was sampled using a saturated sampling technique. All respondents were used to obtain primary data related to the variables, which were collected through a questionnaire with a 1-5-point Likert scale. All data obtained were analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This study found that psychological capital had a significant positive effect on subjective well-being; work engagement moderated the influence of psychological capital on subjective well-being.